Effects of a perioperative geriatric intervention for older adults with Cancer: A randomized clinical trial. Issue 4 (May 2022) - Nipp, Ryan D.; Qian, Carolyn L.; Knight, Helen P.; Ferrone, Cristina R.; Kunitake, Hiroko; Castillo, Carlos Fernandez-del; Lanuti, Michael; Qadan, Motaz; Ricciardi, Rocco; Lillemoe, Keith D.; Temel, Brandon; Hashmi, Ardeshir Z.; et al.
Abstract: Background: Older adults with gastrointestinal cancers undergoing surgery often experience poor outcomes, such as prolonged postoperative hospital length of stay (LOS), intensive care unit (ICU) use, hospital readmissions, and complications. Involvement of geriatricians in the care of older adults with cancer can improve outcomes. We conducted a randomized trial of a perioperative geriatric intervention (PERI-OP) in older patients with gastrointestinal cancer undergoing surgery. Methods: From 9/2016–4/2019, we randomly assigned patients age ≥ 65 with gastrointestinal cancer planning to undergo surgical resection to receive PERI-OP or usual care. Patients assigned to PERI-OP met with a geriatrician preoperatively in the outpatient setting and postoperatively as an inpatient consultant. The primary outcome was postoperative hospital LOS. Secondary outcomes included postoperative ICU use, 90-day hospital readmission rates, and complication rates. We conducted intention-to-treat (ITT) and per-protocol (PP) analyses. Results: ITT analyses included 137/160 patients who underwent surgery (usual care = 68/78, intervention = 69/82). PP analyses included the 68 usual care patients and the 30/69 intervention patients who received the preoperative and postoperative intervention components. ITT analyses demonstrated no significant differences between intervention and usual care in postoperative hospital LOS (7.23 vs 8.21 days, P = 0.374), ICU use (23.2% vs 32.4%, P = 0.257), 90-day hospital readmission rates (21.7% vs 25.0%, P = 0.690), or complication rates (17.4% vs 20.6%, P = 0.668). In PP analyses, intervention patients had shorter postoperative hospital LOS (5.90 vs 8.21 days, P = 0.024), but differences in ICU use (13.3% vs 32.4%, P = 0.081), 90-day hospital readmission rates (16.7% vs 25.0%, P = 0.439), and complication rates (6.7% vs 20.6%, P = 0.137) remained non-significant. Conclusions: In this randomized trial, PERI-OP did not have a significant impact on postoperative hospital LOS, ICU use, hospital readmissions, or complications. However, the subgroup who received PERI-OP as planned experienced encouraging results. Future studies of PERI-OP should include efforts, such as telehealth, to ensure the intervention is delivered as planned.